Peak Myocardial Acceleration during Isovolumic Relaxation Time Predicts the Occurrence of Rehospitalization in Chronic Heart Failure: Data from the Daunia Heart Failure Registry. Issue 4 (15th October 2013) - Correale, Michele; Totaro, Antonio; Ferraretti, Armando; Passero, Tommaso; De, Fiorella; Musaico, Francesco; Ieva, Riccardo; Biase, Matteo Di; Brunetti, Natale Daniele
<x xml:space="preserve">Abstract</x> Background Tissue Doppler imaging (TDI) may be useful in identifying subjects at higher risk among patients with chronic heart failure (CHF). The clinical role of new developed TDI parameters, however, still needs to be documented. Methods A total of 113 consecutive patients with CHF enrolled in the Daunia heart failure registry underwent echocardiography assessment and were followed prospectively for 234 ± 262 days. Conventional echocardiography and TDI parameters were calculated. We also calculated peak myocardial acceleration during isovolumic relaxation time (pIVA[r]) derived from TDI (pIVV(r)/AT). Results Subjects readmitted for worsening HF were characterized by lower levels of pIVA(r) (0.8 ± 0.3 vs. 1.3 ± 0.5 m/s2, P < 0.001). pIVA(r) levels predicted the incidence of readmission for worsening HF during follow‐up (HR 0.78, 95% confidence interval 0.64–0.96, P < 0.05), even after multivariable analysis. The assessment of pIVA(r) in addition to left ventricular ejection fraction (LVEF) and E/E′ provided additional prognostic value (Log Rank P < 0.05). The presence of abnormal pIVA(r), LVEF, and E/E′ levels identified subjects with a higher risk of hospitalization for worsening dyspnea during follow‐up than those with 2 abnormal marker levels or 0–1 (Log Rank P < 0.05). Conclusions Peak myocardial acceleration during isovolumic relaxation time may represent an independent adjunctive tool for the risk stratification of patients with CHF.